2016
DOI: 10.1002/jbm.a.35660
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐based strategies for vascular regeneration

Abstract: Vascular regeneration is known to play an essential role in the repair of injured tissues mainly through accelerating the repair of vascular injury caused by vascular diseases, as well as the recovery of ischemic tissues. However, the clinical vascular regeneration is still challenging. Cell-based therapy is thought to be a promising strategy for vascular regeneration, since various cells have been identified to exert important influences on the process of vascular regeneration such as the enhanced endothelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 163 publications
(310 reference statements)
1
38
0
1
Order By: Relevance
“…The current tissue engineering strategies for repairing large bone defects are faced with unmet vascularization of the implanted grafts . Insufficient blood supply often leads to delayed integration or even failure of the engineered bone constructs . Here, in this study, our findings demonstrated that BFP‐1 could promote the angiogenic functions of EPCs by activating ALK‐1/Smad pathway in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current tissue engineering strategies for repairing large bone defects are faced with unmet vascularization of the implanted grafts . Insufficient blood supply often leads to delayed integration or even failure of the engineered bone constructs . Here, in this study, our findings demonstrated that BFP‐1 could promote the angiogenic functions of EPCs by activating ALK‐1/Smad pathway in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tissue engineered bone grafts have shown great potentials in repairing bone defects with the benefits of various materials and feasible process of fabrication . However, lack of vascularization hinders the engineered bone grafts to comply with host tissues, and necrosis of the core area in grafts often occurs . Therefore, enhancement of the vascularization in tissue engineered bone substitutes is of vital importance to improve the effect of bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical utility of small‐diameter (<6 mm) vascular grafts is still a thorny challenge because of thrombosis or intimal hyperplasia . Rational regulation of physiological activity of vascular endothelial cells (VECs) and vascular smooth muscle cells (VSMCs) is effective for rapid endothelialization, hyperplasia inhibition and consequent long‐term patency …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, substrates also must support stem cells as these cells are vital to the long-term viability of the transplants for a variety of tissues. 2224 In addition, the substrate must be sufficiently porous to allow for free diffusion of glucose, proteins, and ions, as well as in-growth of regenerating nerves and blood vessels to penetrate through the membrane.…”
mentioning
confidence: 99%